Phylogeography of Himalrandia lichiangensis from the dry-hot valleys in Southwest China - Qiao, Yaomei; Liu, Jian; Gong, Xun (Frontiers in Plant Science, 2022)
Both tectonic movements (e.g., orogenesis) and climatic oscillations (e.g., glaciation) may shape the phylogeographical patterns of plant species in different time scales. However, how these two processes interact to comprehensively impact plant distributions and divergence remain relatively little explored. The dry-hot valleys in Southwest China are overlapped with the Hengduan Mountains (HDM) and harbor a high number of endemic plants. In this study, we investigated the evolutionary history and potential distribution of Himalrandia lichiangensis, an endemic shrub of the Rubiaceae family, to evaluate the effects from tectonic and climatic processes on this thermophilic plant species from the dry-hot valleys of HDM. By sequencing data from four plastid non-coding regions (psbM-trnD, trnD-trnT, atpB-rbcL and accD-psaI) and two single-low copy nuclear genes (CAMX and ITS) for 423 individuals from 23 populations, we investigated the genetic diversity, phylogeographical pattern and population dynamics of H. lichiangensis. We found a high degree of differentiation in H. lichiangensis that dates to a Miocene divergence (~13 Mya), accompanied by frequent orogeneses in this period. This hypothesis is also supported by the association between genetic differentiation and altitudinal gradients among populations. The Middle Jinsha River valley, which harbors the greatest genetic diversity, is most likely to be a refuge for H. lichiangensis during the Quaternary glaciations. We also detected a strong barrier effect between the Nanpan River and Jinsha River, suggesting the river system may play a role in geographical isolation between clades on both sides of the barrier. The Maximum Entropy Model (MaxEnt) result showed that future climate warming will lead to the niche expansion in some areas for H. lichiangensis but will also cause a scattered and fragmented distribution. Given the high among-population differentiation and no recent expansion detected in H. lichiangensis, its current phylogeographical pattern is possibly due to a long-term geographical barrier that caused by uplifting of HDM in Miocene, as well as Quaternary climate refugia isolated by multiple river systems. This study illustrated how tectonic and climatic processes may act in succession to shape plant phylogeography and offers insights into the origin of biodiversity and endemism in the dry-hot valleys of southwest China.